The effects of Transcutaneous Electrical Nerve Stimulation on postural control in patients with chronic low back pain - Rojhani-Shirazi, Z (J Med Life, 2015)
Objective: The effects of transcutaneous electrical nerve stimulation (TENS) on postural control in patients with low back pain which is not well known. This study aimed to evaluate the effects of TENS on postural control in chronic low back pain. Methods: This study was an experimental research design. Twenty-eight patients with chronic LBP (25-45 Y/ O) participated and by using a random allocation, were divided to samples who participated in this study. The mean center of pressure (COP) velocity and displacement were measured before, immediately and 30 min after the intervention. The tests were done with eyes open and closed on a force platform. Sensory electrical stimulation was applied through the TENS device. The descriptive statistics, independent sample T-test and ANOVA with repeated measurement on time were used for data analysis. Results: The results of the present study demonstrated that the application of the sensory electrical stimulation in chronic LBP patients showed a statistically significant improvement in postural control in Medio-lateral direction with no corresponding effect on the anterior-posterior direction immediately following the TENS application and 30 minutes after it in closed eyes conditions as compared to baseline. The application of TENS decreased the displacement and velocity of COP (p≤0.05), 30 minutes after the application of sensory electrical stimulation. The results showed that the mean displacement and velocity of COP decreased in eyes open position (p≤0.05). Also, immediately and 30 minutes after the application of sensory electrical stimulation, COP displacement and velocity in ML direction with eyes closed significantly decreased in the intervention group in comparison with control group (p≤0.05). Conclusion: The application of TENS in patients with chronic low back pain could improve postural control in these patients.